Literature Study: Types of Social Support in Adolescents with Unwanted Pregnancy - Sifva Fauziah; Ermiati Ermiati; Eka Afrima Sari (Department of Nursing, Faculty of Health Sciencce, Universitas Brawijaya, 2021)
Unwanted Pregnancy in adolescents can create a negative impact on adolescents who experience it. Management of Unwanted Pregnancy by providing social support are needed to reduce the perceived impact. The limited articles on the types of social support for adolescents experiencing Unwanted Pregnancy made this literature study aimed to find out the types of social support that can be provided to adolescents who experience Unwanted Pregnancy. This research method was scoping review using search engines such as EBSCOHost, Google Scholar, and PubMed. The keywords used were